Teknologi Smart Conservation Untuk Identifikasi Spesies Mangrove Di Kawasan Ekowisata Cuku Nyinyi, Lampung - Triyana Muliawati; Fuji Lestari; Mika Alvionita Sitinjak; Eristia Arfi; Devia Gahana Cindi Alfian (CV. Multi Kreasi Media, 2025)
Mangroves are a type of forest ecosystem that grows in coastal areas along tropical and subtropical shores throughout Indonesia, particularly in Lampung Province. This ecosystem is found in regions influenced by tidal seawater. Mangroves consist of various species of trees, shrubs, and other plants that can survive in highly saline and muddy environments. Additionally, mangroves provide numerous benefits for environmental sustainability and human well-being. A healthy mangrove ecosystem contains diverse plant species with specific characteristics that help maintain ecological balance and ensure optimal ecological functions.Lampung Province has a mangrove ecotourism site located in Sidodadi Village, Teluk Pandan District, Pesawaran Regency, known as Cuku Nyinyi. Uniquely, Cuku Nyinyi is often used as a research and learning site for students, researchers, and the general public to study mangroves.One of the challenges faced by the ecotourism management team, the Bina Jaya Lestari Forest Farmers Group (KTH), is the difficulty in identifying and classifying mangrove species planted in the Cuku Nyinyi ecotourism area. Additionally, there is a lack of adequate information about mangroves, such as their age, anatomy, habitat, environmental adaptations, benefits, and other relevant details. To address this issue, researchers are developing an automatic identification system for mangrove species based on leaf morphology using a Convolutional Neural Network (CNN) approach. CNN is one of the most effective methods for pattern recognition in images and mangrove image processing. This technology is expected to be implemented in the form of a camera application that can automatically identify information from an image of mangrove leaf morphology captured in the Cuku Nyinyi ecotourism area.The Mangrove Camera Application provides new insights to KTH and the general public regarding the potential and importance of conserving natural resources.